International Business Expansion: The Roles of Affiliation and Ownership - Wright, Roxana (International Journal of Business, Economics and Management, 2020)
The study provides a unique perspective that transcends firm motivations to understand business expansion outcomes, investigating the expansion connection with geography and the characteristics of the companies that pursue it. Specifically, the research evaluates whether selected factors related to the origin and location of expansion, the company’s ownership status and affiliation, and the home and host regions predict a company’s expansion actions as international or domestic. The study uses a random sampling research design and a large sample of instances of company expansion, defined broadly as direct and indirect investments and business development actions. The procedure investigates the phenomenon over the long run, with a focus on prediction. The analysis concludes that affiliation position determines expansion type, with parent companies more likely to pursue international expansion. The paper also offers better understanding of the regions where international business development is more likely, with comparative findings in North America and Europe.